2001
DOI: 10.1007/s005850000303
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the interplanetary medium on SuperDARN radar scattering occurrence

Abstract: Abstract. The eects of the characteristics of the interplanetary medium on the radar scattering occurrence, related to the whole array of SuperDARN radars installed in the Northern Hemisphere, have been studied over a two-year period. Statistically signi®cant correlations of the variation of the scattering occurrence are found with the merging electric ®eld and with the negative B z component of the interplanetary magnetic ®eld, independent of the seasonal period considered. This result demonstrates that the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
18
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(23 citation statements)
references
References 13 publications
5
18
0
Order By: Relevance
“…This delay is set equal to 1 hour because this value optimizes the correlation between ground‐based and interplanetary measurements in our data set. In addition, the approximation of a 1‐hour delay is in agreement with previous estimations of average delays between satellites and ground‐based measurements [e.g., Arnoldy , 1971; Ballatore et al , 2001]. The results that we obtain with this average delay are qualitatively similar to the results obtained with a slightly different delay or, in particular, to the results obtained with a more accurate calculation of the delays at specific times.…”
Section: Data Analysis and Experimental Observationssupporting
confidence: 90%
“…This delay is set equal to 1 hour because this value optimizes the correlation between ground‐based and interplanetary measurements in our data set. In addition, the approximation of a 1‐hour delay is in agreement with previous estimations of average delays between satellites and ground‐based measurements [e.g., Arnoldy , 1971; Ballatore et al , 2001]. The results that we obtain with this average delay are qualitatively similar to the results obtained with a slightly different delay or, in particular, to the results obtained with a more accurate calculation of the delays at specific times.…”
Section: Data Analysis and Experimental Observationssupporting
confidence: 90%
“…They concluded that the ionospheric electron density controls the onset of echoes at a specific range, thus advocating refraction as a key factor for echo detection. Ballatore et al [2001] found that there is a statistically significant correlation between Northern Hemisphere radar echo occurrence and negative interplanetary magnetic field B z values, independent of season. Parkinson et al [2003] considered 1 year (1999)(2000) of echo statistics for the Australian SuperDARN radar and noticed a March (autumn) maximum, though the overall seasonal variation was, apparently, not significant.…”
Section: Review Of Previous Hf Studiesmentioning
confidence: 83%
“…Ballatore et al . [] found that there is a statistically significant correlation between Northern Hemisphere radar echo occurrence and negative interplanetary magnetic field B z values, independent of season. Parkinson et al .…”
Section: Review Of Previous Hf Studiesmentioning
confidence: 98%
“…The IMF variations have been previously shown to affect HF radar observations of the auroral ionosphere in both the F region [ Ballatore et al , ] and E region [ Makarevich et al , ]. The IMF variations are a consequence of solar activity and are not related to the time of day or season, so they must be studied independently.…”
Section: Observationsmentioning
confidence: 99%
“…In addition to direct effects of solar illumination, there is also interest in the indirect ways in which the Sun may control irregularity production in the ionosphere. It has been shown that negative IMF B z generally leads to higher echo occurrence in the auroral F region [ Ballatore et al , ]. Even stronger IMF control has been demonstrated for the auroral E region irregularities [ Makarevich et al , ].…”
Section: Introductionmentioning
confidence: 99%